Perizinan Lingkungan Sebagai Upaya Mengendalikan Pencemaran Akibat Industrial Waste Sesuai Undang-Undang Nomor 6 Tahun 2023 - Dea Amalia Novela; Sadino; Aris Machmud (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This journal examines environmental permits in the enforcement of current legislative rules aimed at mitigating industrial pollution. The author elucidates that the issue of environmental pollution stemming from industrial waste has emerged as a global concern, as it poses a threat to human health and environmental sustainability. Despite the existence of legislation concerning environmental contamination, numerous infractions continue to be perpetrated by industry. The urgency of this research is considering that the environmental permit policy is a preventive government tool as an effort to control community behavior, and also repressive in overcoming environmental problems caused by human activities. Environmental licenses are a crucial governmental regulation designed to safeguard the environment from industrial waste contamination, thereby preventing harm that could adversely affect the community. Consequently, obtaining an environmental permit is crucial for implementing legislation pertaining to environmental protection, ensuring that industries adhere to established standards and are accountable for their waste production. The author asserts that robust environmental legislation may eliminate industrial waste contamination. Nevertheless, sustained collaboration is essential among all stakeholders, including the government, industry, and society, to guarantee the success of these initiatives.